2017
DOI: 10.1016/j.ijpddr.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Novel carbazole aminoalcohols as inhibitors of β -hematin formation: Antiplasmodial and antischistosomal activities

Abstract: Malaria and schistosomiasis are two of the most socioeconomically devastating parasitic diseases in tropical and subtropical countries. Since current chemotherapeutic options are limited and defective, there is an urgent need to develop novel antiplasmodials and antischistosomals. Hemozoin is a disposal product formed from the hemoglobin digestion by some blood-feeding parasites. Hemozoin formation is an essential process for the parasites to detoxify free heme, which is a reliable therapeutic target for ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Spectroscopic investigations revealed that 100 possessed a promising binding affinity with free heme moieties (IC 50 = 55.43 ± 6.78 µM) . Duan et al identified a series of novel carbazole amino alcohols ( 102 ) as potential antiplasmodial and antischistosomal agents and correlated the inhibitory activity of β‐hematin formation and antiparasitic activity through investigations on dual antiparasitic mechanisms . The xanthone derivatives were extracted from the sea urchin Strongylocentrotus purpuratus , and the identification of the antimalarial activity was serendipitous .…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 99%
“…Spectroscopic investigations revealed that 100 possessed a promising binding affinity with free heme moieties (IC 50 = 55.43 ± 6.78 µM) . Duan et al identified a series of novel carbazole amino alcohols ( 102 ) as potential antiplasmodial and antischistosomal agents and correlated the inhibitory activity of β‐hematin formation and antiparasitic activity through investigations on dual antiparasitic mechanisms . The xanthone derivatives were extracted from the sea urchin Strongylocentrotus purpuratus , and the identification of the antimalarial activity was serendipitous .…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 99%
“…This skeleton is present in many biologically active compounds [ [26] , [27] , [28] ]. One of the most important properties of the carbazole-core agent is antiplasmodial activity [ [29] , [30] , [31] ]. Many recently published reports confirmed also that carbazole-based compounds exert promising antibacterial [ 32 ], antiviral [ 33 ], antifungal [ 34 ] and antiparasite [ 35 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 20a Antiplasmodial and antischistosomal activities: Weisi Wang et al (2017) synthesized carbazole amino alcohols derivatives. The compounds were tested for invitro anti-plasmodial and antischistosomal activity againstPlasmodium falciparum 3D7 and Dd2 strains and adult and juvenileSchistosoma japonicum.by P. falciparum whole cell assay using Chloroquine and dihydroartemisinin as stanadard drugs.The result shows that the compound 21a exhibit potent dual anti-parasitic activities27 .…”
mentioning
confidence: 99%